United in diversity: Multilingual language policy and democracy building in the EU - Szabo, Orsolya Katalin (European Scientific Journal, ESJ, 2024)
The present study undertakes to examine how plurilingual practices in a political entity relate to the principles of democracy, with a particular focus on the European Union. In academia, there are different theories as to the compatibility of democracy with linguistic fragmentation. These faultlines are mostly rooted in different perceptions of democratic citizenship. The present essay will take a closer look at the state-of-the-art of scientific literature with regard to the subject. The compatibility of multilingualism with democracy is all the more fascinating when examining the subject at transnational level, in the institutional realm of the European Union, a transnational entity exploding the framework of a traditional international organization.